Negation of Place in the Poetry of Palestinian Women - Sliman-Baraky, Rawand (International Journal of Language and Literary Studies, 2023)
This article aims to clarify both the function of the negation of place in the poetry of Palestinian women and the feminist thought that this negation generates. For these purposes, it presents “Nu??? al-mak?n” [Texts of Place] in the collection Kh?rij al-Fu??l Ta?allamtu al-?ayar?n [Out of the Seasons I Learned to Fly] (Hlewa, 2016) by Sh?kha ?il?w? (born 1968). Criticizing one’s place and leaving it reflects a determination to achieve a specific goal. When talking about the Palestinian Arab woman, it appears that she is in two places; one is the patriarchal society around her, and the second is being part of a national minority in a broader society. The process of leaving one’s place is more complex for her than for her male counterparts; the risk of her leaving her place is two-fold because there is a greater lack of security and confidence in reaching a safe place where her dreams can be realized. Leaving her place means opening her mind to even broader aspects than either her society or culture dictates. These broader aspects include the search for what is suitable for women and what enables them to grow as full human beings, using all their faculties and actualizing all their dreams.